The Potential of Refugia Plants in Increasing Arthropoda Diversity of Rice in South Solok Regency - Yunisman, Yunisman; Annisa, Annisa; Hartatiana, Jenny; Syahrawati, My; Busniah, Munzir; Hamid, Hasmiandy; Lina, Eka Candra (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2026)
The conservation of natural enemies through the use of refugia plants is an important strategy to enhance arthropod diversity and stability in rice ecosystems, but its effectiveness may vary across locations. This study aimed to evaluate the potential of several refugia plant species in increasing arthropod diversity in rice fields of South Solok Regency, Indonesia. The study was conducted from December 2024 to April 2025 in Nagari Lubuk Gadang, South Solok Regency. Arthropod sampling was performed using a D-VAC (vacuum sampler) and insect net. The experiment was arranged in a randomized block design with six treatments (Cosmos caudatus, Ageratum conyzoides, Portulaca oleracea, Celosia cristata, Tagetes erecta, control), in four replications respectively. Observations included species composition, abundance, and diversity indices. The results showed that refugia plants contributed to the suppression of pest populations and improved the stability of arthropod communities. A total of 9 orders, 32 families, and 44 species were recorded, comprising 1,167 individuals, with herbivores accounting for 71.55% of the total population. The dominant herbivores were Cicadulina bipunctata, Leptocorisa oratorius, and Nilaparvata lugens, which were generally more abundant in rice fields without refugia. Predator and parasitoid abundance tended to be higher in the rice fields surrounded by C. cristata and T. erecta. The highest arthropod diversity was recorded in plots with T. erecta (H’ = 3.02), low dominance (0.07) and high evenness (0.86). Therefore, C. cristata and T. erecta are recommended as refugia plants to support sustainable integrated pest management in rice fields of mid-altitude areas.